A perovskite solar cell and its fabrication method
By using halogenated N,N-dialkylbenzimidazole salts in perovskite solar cells to form a one-dimensional passivation layer, the perovskite solar cell stability problem is solved and higher photoelectric conversion efficiency and stability are achieved. .
Patent Information
- Application Number
- CN202110294571.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-03-19
AI Technical Summary
Perovskite solar cells have challenges in stability, especially due to structural decomposition and performance degradation due to the diffusion of halogen ions.
The surface of the perovskite light-absorbing layer is treated with halogenated N,N-dialkylbenzimidazolium salts to form a one-dimensional passivation layer to block water vapor and ion diffusion.
It improves the water stability and working stability of perovskite solar cells, reduces the defect state density on the surface of the light-absorbing layer, and improves the photoelectric conversion efficiency and stability.
Smart Images

Figure CN115117250B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electroluminescent devices, and in particular to a perovskite solar cell and a preparation method thereof. Background Art
[0002] Organic-inorganic hybrid perovskite materials have excellent optical and electronic properties, such as high absorption coefficient, long charge carrier diffusion length and low defect density, and tunable band gap. Solar cells (PSCs) based on this material have achieved great progress in power conversion efficiency. However, the stability issues faced by PSCs still pose a huge challenge for future large-scale applications. The main instability problem is attributed to the inherent weak binding force of halide perovskite materials, where the diffusion of halides can lead to the decomposition of the perovskite structure and the degradation of device performance (especially under conditions of light, heat, electric field, moisture, etc.). Therefore, it is urgent to control the halogen diffusion process to achieve long-term working stability in high-efficiency perovskite devices.
[0003] In general, the stability of small-area PSCs is mainly limited by the diffusion of halogen ions in the vertical direction, that is, from the perovskite layer to the charge transport layer and then to the electrode layer. How to effectively inhibit the diffusion and migration of ions is crucial to improving the performance of the device. The stability of high-efficiency perovskite solar modules is much worse than that of small-area PSCs, and the degradation mechanism is more complicated. In the industrialization of perovskite cells, the stability of PSC modules is an important consideration. The module contains an array of sub-cells with series interconnections, and the scribed perovskite film is partially exposed to the metal electrode or air. Even with additional packaging to exclude the entry of humid air, these unfavorable contact points provide additional channels for ion diffusion in the perovskite. Therefore, it is necessary to inhibit the ion diffusion channels of vertical diffusion and lateral diffusion within the PSC module. The first is vertical diffusion, which is usually observed in small-area PSCs. The surface diffusion of ions perpendicular to the light-absorbing layer. The second is lateral diffusion that occurs parallel to the substrate, that is, the interconnection area between sub-cells, which can seriously affect the stability of the module. How to inhibit ion diffusion from causing irreversible degradation is a problem that must be solved.
[0004] In patent CN111430552A, the invention introduces a 2D perovskite protective layer to protect the exposed surface after the 2D perovskite film layer is cut. The 2D structure can temporarily avoid water and oxygen erosion and chemical reactions of metal-halogen ions, but the 2D structure will undergo a phase transition with the perovskite to form a 2D-3D low-dimensional mixed structure, which is not conducive to the long-term stability of the device. Therefore, it is urgent to develop a simple and easy perovskite film passivation method to improve the long-term stability of the device. Summary of the invention
[0005] One purpose of the present invention is to solve the existing problems and propose the following technical solutions:
[0006] On one hand, the present invention provides a perovskite solar cell, comprising a conductive substrate, an electron transport layer, a perovskite light absorbing layer, a modification layer, a hole transport layer and a back electrode layer stacked in sequence, wherein the modification layer is a one-dimensional passivation layer; the general formula of the perovskite light absorbing layer material is ABXn, and the general formula of the modification layer material is MBXn, wherein M is N,N-dialkylbenzimidazole.
[0007] Furthermore, the thickness of the modified layer is 5 to 40 nm.
[0008] More preferably, the thickness of the modified layer is 10 to 30 nm.
[0009] Furthermore, the thickness of the perovskite light absorbing layer is 100 to 1000 nm.
[0010] Furthermore, the thickness of the electron transport layer is 10 to 200 nm.
[0011] Furthermore, the thickness of the hole transport layer is 20-200 nm.
[0012] Furthermore, the back electrode layer adopts a gold electrode or a carbon-based electrode, and the thickness of the gold electrode is 30 to 300 nm.
[0013] Further, the M is selected from C6H5C2H4NH3 + 、CH3C3H6NH3 + 、COOH(CH2)4NH3 + 、CH3NH3 + 、HC(NH2)2 + , Cs + and Rb + At least one of .
[0014] Further, the B is pb 2+ Sn 2+ and Ge 2+ At least one of .
[0015] Furthermore, the X is a halogen ion.
[0016] More preferably, the halogen ion is selected from at least one of fluorine, chlorine, bromine and iodine.
[0017] Furthermore, the N,N-dialkylbenzimidazolyl is selected from at least one of N,N-dimethylbenzimidazolyl, N,N-diethylbenzimidazolyl, N,N-diisopropylbenzimidazolyl and N,N-dihexylbenzimidazolyl.
[0018] Another aspect of the present invention provides a method for preparing a perovskite solar cell, comprising the following steps:
[0019] S1: prepare the perovskite (ABXn) light absorbing layer precursor solution, where X is a halogen ion;
[0020] S2: pre-treated conductive glass / electron transport layer substrate;
[0021] S3: coating the precursor solution prepared in S1 on the substrate, and then performing annealing treatment to obtain a perovskite (ABXn) light absorbing layer;
[0022] S4: preparing halogenated N, N-dialkylbenzimidazole salt: firstly mixing benzimidazole, K2CO3 and CH3CN, stirring, then adding alkyl halide dropwise to obtain a mixed solution, stirring, extracting and drying to obtain halogenated N, N-dialkylbenzimidazole salt; the halogen element in the alkyl halide is consistent with the X element in the perovskite (ABXn) light absorbing layer in step S1;
[0023] S5: dissolving the prepared halogenated N,N-dialkylbenzimidazole salt in an organic solvent, scraping or spin coating it on the perovskite (ABXn) light absorbing layer, and annealing to obtain a modified layer, wherein the modified layer is a one-dimensional passivation layer.
[0024] S6: forming a hole transport layer on the surface of the modified layer;
[0025] S7: forming a back electrode layer on the surface of the hole transport layer.
[0026] Furthermore, the perovskite light absorbing layer precursor solution can be coated on the electron transport layer of the substrate by at least one of spin coating, doctor blade coating, pulling method, slit coating method and spray coating method.
[0027] Furthermore, in step S4, the alkyl halide is selected from at least one of methyl iodide, ethyl iodide, hexyl iodide, isopropyl iodide, methyl bromide, ethyl bromide, hexyl bromide, isopropyl bromide, methyl chloride, ethyl chloride, hexyl chloride, and isopropyl chloride.
[0028] Furthermore, in step S4, the stirring temperature of the mixed solution is 80 to 120° C., and the stirring time is 48 to 120 hours.
[0029] Furthermore, in step S5, the concentration of the halogenated N,N-dialkylbenzimidazole salt in the organic solvent is 0.5-10 mg / mL.
[0030] Furthermore, in step S5, the spin coating speed is 4000-6000 rpm / min, the spin coating time is 20-50 s; the scraping speed is 50-500 mm s -1 .
[0031] Furthermore, in the step S5, the heating temperature of the annealing treatment is 50-200° C., and the heating time is 5-30 min.
[0032] Furthermore, in the step S5, the thickness of the modified layer is 5 to 40 nm; more preferably, the thickness of the modified layer is 10 to 30 nm.
[0033] Furthermore, in step S5, the organic solvent is selected from at least one of isopropanol, methanol, dichloroethane, chloroform, and chlorobenzene.
[0034] Furthermore, in step S2, the pretreatment conditions are: annealing at 100-200° C. for 10-50 min in an air atmosphere.
[0035] Furthermore, the electron transport layer is an n-type inorganic semiconductor or an n-type organic semiconductor, and the n-type inorganic semiconductor or the n-type organic semiconductor includes but is not limited to at least one of the group consisting of PCBM, TiO2, mesoporous TiO2, SnO2, ZnO or ZnO-ZnS.
[0036] Furthermore, the electron transport layer is one of SnO2, TiO2 / SnO2, ZnO-ZnS / mesoporous TiO2 and TiO2 / mesoporous TiO2; SnO2 is further preferred.
[0037] Furthermore, the hole transport layer is a p-type inorganic or p-type organic semiconductor, and the p-type inorganic or p-type organic semiconductor includes but is not limited to: NiOx, CuSCN, spiro-OMeTAD, P3HT or PTAA; more preferably spiro-OMeTAD.
[0038] Beneficial Effects
[0039] 1. The present invention uses halogenated N, N-dialkylbenzimidazole salts to treat the surface of the three-dimensional perovskite light-absorbing layer, which can be in-situ converted on the surface to form a uniform and dense one-dimensional passivation layer.
[0040] 2. The perovskite light-absorbing layer with one-dimensional passivation structure modification prepared by the present invention can block water vapor from penetrating into the battery and module, thereby improving the water stability of the device.
[0041] 3. The present invention proposes that the one-dimensional passivation layer modification layer of the perovskite solar cell can block the longitudinal and lateral diffusion of halides in the module, thereby improving the working stability of the module.
[0042] 4. The one-dimensional passivation layer prepared by the present invention can reduce the defect state density on the surface of the perovskite light-absorbing layer. The solar module assembled based on the perovskite treated by this method has high photoelectric conversion efficiency and stability.
[0043] 5. The one-dimensional passivation structure modification layer prepared by the present invention is very stable after annealing treatment and will not continue to react with the three-dimensional perovskite light-absorbing layer structure to form a mixed-dimensional structure. The present invention ensures that the device structure has longer-term stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 These are the SEM images and schematic diagrams of the conformal in-situ passivation structure of the one-dimensional structure modification layer of the present invention.
[0045] Figure 2 The crystal structure diagram of the one-dimensional passivation layer of the modified layer prepared based on N, N-diisopropylbenzimidazole in the present invention (a), the schematic diagram after processing the perovskite light-absorbing layer (b), and the XRD diagram (c).
[0046] Figure 3 is the N, N-diisopropylbenzimidazole iodide in Example 3 of the present invention. 1 H NMR characterization chart.
[0047] Figure 4 The XRD diagrams of the one-dimensional structure modification layers prepared based on different halogenated N,N-dialkylbenzimidazole salts in Examples 1-4 and Comparative Example 1 of the present invention are shown.
[0048] Figure 5 This is a comparison chart of the efficiency curves of perovskite solar cells using one-dimensional structure modification layers prepared based on different halogenated N,N-dialkylbenzimidazole salts in Examples 1-4 of the present invention and Comparative Example 1.
[0049] Figure 6 The graphs are a comparison of cell efficiency curves (a) and a comparison of stability curves (b) of perovskite solar cells with one-dimensional structure modification layers prepared based on imidazole and benzimidazole in Example 3 of the present invention and Comparative Examples 1-2.
[0050] Figure 7 This is a comparison chart of cell efficiency curves of perovskite solar cells using one-dimensional structure modification layers prepared based on different halogen anions in the present invention.
[0051] Figure 8 1 and 1. The module efficiency curve comparison diagram (a) and the stability curve comparison diagram (b) of Example 7 of the present invention and Comparative Example 3 before and after the one-dimensional structure modification layer is passivated. DETAILED DESCRIPTION
[0052] The following describes the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0053] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for the understanding and reading of people familiar with this technology, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size should fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "inner", "outer", "bottom", "one", "middle" and so on quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.
[0054] On the one hand, the present invention provides a perovskite solar cell, comprising a conductive substrate, an electron transport layer, a perovskite light absorbing layer, a modification layer, a hole transport layer and a back electrode layer stacked in sequence, characterized in that the modification layer is a one-dimensional passivation layer; the general formula of the perovskite light absorbing layer material is ABXn, and the general formula of the modification layer material is MBXn, wherein M is N,N-dialkylbenzimidazole.
[0055] According to an embodiment of the present invention, the thickness of the one-dimensional passivation modification layer is 5-40 nm; preferably, the thickness of the one-dimensional passivation modification layer is 10-30 nm. Figure 1 The SEM image and schematic diagram of the conformal in-situ passivation structure of the one-dimensional structure modification layer of the present invention are shown in FIG. Figure 1 It can be seen that the present invention uses benzimidazole-based ions to treat the three-dimensional perovskite light-absorbing layer, and in situ forms a one-dimensional structure with a thickness of about 30 nm on its surface. The modified layer is dense and uniform, and has good stability. It can inhibit the vertical diffusion of ions in the PSC battery, as well as the vertical and lateral ion diffusion in the module. The formed one-dimensional modified layer will not form a mixed structure with the three-dimensional perovskite, and will not affect the charge transfer at the interface, thereby improving the efficiency and stability of the battery.
[0056] According to an embodiment of the present invention, the N,N-dialkylbenzimidazolyl group is selected from one or more of N,N-dimethylbenzimidazolyl, N,N-diethylbenzimidazolyl, N,N-diisopropylbenzimidazolyl, and N,N-dihexylbenzimidazolyl; in a specific embodiment of the present invention, the N,N-dialkylbenzimidazolyl group can be selected from N,N-dimethylbenzimidazolyl, N,N-diethylbenzimidazolyl, N,N-diisopropylbenzimidazolyl, and N,N-dihexylbenzimidazolyl. Any one of the N, N-dihexylbenzimidazole groups can also be selected from any one of the combinations thereof, such as a combination of two N, N-dialkylbenzimidazole groups, N, N-dimethylbenzimidazole group and N, N-diisopropylbenzimidazole group, or a combination of three N, N-dialkylbenzimidazole groups, N, N-dimethylbenzimidazole group, N, N-diethylbenzimidazole group and N, N-dihexylbenzimidazole group, or other combinations. By using different N, N-dialkylbenzimidazole groups to mix and treat the obtained modified layer, several different one-dimensional structures can be achieved.
[0057] According to an embodiment of the present invention, the thickness of the perovskite light absorbing layer is 100-1000 nm.
[0058] According to an embodiment of the present invention, the thickness of the electron transport layer is 10-200 nm.
[0059] According to an embodiment of the present invention, the thickness of the hole transport layer is 20-200 nm.
[0060] According to an embodiment of the present invention, the back electrode layer adopts a gold electrode or a carbon-based electrode; wherein the thickness of the gold electrode is 30-300 nm.
[0061] According to an embodiment of the present invention, M is selected from C6H5C2H4NH3 + 、CH3C3H6NH3 + 、COOH(CH2)4NH3 + 、CH3NH3 + 、HC(NH2)2 + , Cs + and Rb + One or more of .
[0062] According to an embodiment of the present invention, B is Pb 2+ Sn 2+ and Ge 2+ One or more of .
[0063] According to an embodiment of the present invention, X is a halogen ion; preferably, the halogen ion is selected from one or more of fluorine, chlorine, bromine and iodine.
[0064] According to an embodiment of the present invention, the N,N-dialkylbenzimidazolyl is selected from one or more of N,N-dimethylbenzimidazolyl, N,N-diethylbenzimidazolyl, N,N-diisopropylbenzimidazolyl and N,N-dihexylbenzimidazolyl. Figure 2 The present invention is based on the one-dimensional passivation layer crystal structure diagram (a) of the modified layer prepared by N, N-diisopropylbenzimidazole, the schematic diagram after treating the perovskite light-absorbing layer (b), and the XRD diagram (c). From the one-dimensional crystal structure (Figure a), the N, N-diisopropylbenzimidazole cations are distributed around the one-dimensional chain composed of Pb-I octahedrons. The structure of the entire one-dimensional perovskite is stabilized by the van der Waals force between N, N-diisopropylbenzimidazole molecules and the electrostatic force with the one-dimensional Pb-I chain. XRD test shows that a new peak of 8.09° appears on the surface of the perovskite film treated with iodinated N, N-diisopropylbenzimidazole, which just coincides with the characteristic peak of the one-dimensional crystal simulation XRD. In summary, the iodinated N, N-diisopropylbenzimidazole treatment of the perovskite film surface will form a 1D perovskite structure in situ.
[0065] The present invention also provides a method for preparing a perovskite solar cell, comprising the following steps:
[0066] S1: prepare the perovskite (ABXn) light absorbing layer precursor solution, where X is a halogen ion;
[0067] S2: pre-treated conductive glass / electron transport layer substrate;
[0068] S3: coating the precursor solution prepared in S1 on the substrate, and then performing annealing treatment to obtain a perovskite (ABXn) light absorbing layer;
[0069] S4: preparing halogenated N, N-dialkylbenzimidazole salt: firstly mixing benzimidazole, K2CO3 and CH3CN, stirring, then adding alkyl halide dropwise to obtain a mixed solution, stirring, extracting and drying to obtain halogenated N, N-dialkylbenzimidazole salt; the halogen element in the alkyl halide is consistent with the X element in the perovskite (ABXn) light absorbing layer in step S1;
[0070] S5: dissolving the prepared halogenated N,N-dialkylbenzimidazole salt in an organic solvent, scraping or spin coating it on the perovskite (ABXn) light-absorbing layer, and annealing to obtain a modified layer, which is a one-dimensional passivation layer.
[0071] S6: forming a hole transport layer on the surface of the modified layer;
[0072] S7: forming a back electrode layer on the surface of the hole transport layer.
[0073] According to an embodiment of the present invention, the perovskite light absorbing layer precursor solution can be coated on the electron transport layer of the substrate by at least one of spin coating, doctor blade coating, Czochralski coating, slit coating and spray coating.
[0074] According to an embodiment of the present invention, in step S4, the alkyl halide is selected from one or more of methyl iodide, ethyl iodide, hexyl iodide, isopropyl iodide, methyl bromide, ethyl bromide, hexyl bromide, isopropyl bromide, methyl chloride, ethyl chloride, hexyl chloride, and isopropyl chloride; the length of the alkyl chain in the alkyl halide is not limited to the above-mentioned methyl, ethyl, isopropyl, and hexyl.
[0075] According to an embodiment of the present invention, in step S4, the stirring temperature of the mixed solution is 80-120° C., and the stirring time is 48-120 h.
[0076] According to an embodiment of the present invention, in step S5, the concentration of the halogenated N,N-dialkylbenzimidazole salt in the organic solvent is 0.5-10 mg / mL.
[0077] According to an embodiment of the present invention, in step S5, the speed of spin coating is 4000-6000 rpm / min, the time of spin coating is 20-50 s; the speed of scraping is 50-500 mm s -1 The scraping time is determined by the size of the substrate area.
[0078] According to an embodiment of the present invention, in step S5, the heating temperature of the annealing treatment is 50-200° C., and the heating time is 5-30 min.
[0079] According to an embodiment of the present invention, in step S2, the pretreatment conditions are: annealing in an air atmosphere at a temperature of 100-200° C. for 10-50 min.
[0080] According to an embodiment of the present invention, in step S5, the organic solvent is selected from one or more of isopropanol, methanol, dichloroethane, chloroform, and chlorobenzene.
[0081] According to an embodiment of the present invention, the electron transport layer is an n-type inorganic semiconductor or an n-type organic semiconductor, wherein the n-type inorganic semiconductor or the n-type organic semiconductor includes but is not limited to: at least one of the group consisting of PCBM, TiO2, mesoporous TiO2, SnO2, ZnO or ZnO-ZnS; according to an embodiment of the present invention, the electron transport layer is one or more of SnO2, TiO2 / SnO2, ZnO-ZnS / mesoporous TiO2 and TiO2 / mesoporous TiO2; preferably, in a specific embodiment, the electron transport layer is SnO2, SnO2 has a good energy level match with the perovskite light absorbing layer, good stability, and can effectively transport electrons to the back electrode layer, thereby ensuring high photoelectric conversion efficiency.
[0082] According to an embodiment of the present invention, the hole transport layer is a p-type inorganic or p-type organic semiconductor, and the p-type inorganic or p-type organic semiconductor includes but is not limited to: NiOx, CuSCN, spiro-OMeTAD, P3HT or PTAA; preferably, in a specific embodiment, the hole transport layer is spiro-OMeTAD, which has a good energy level match with the perovskite light absorbing layer and can effectively transport holes to the back electrode layer, thereby ensuring high photoelectric conversion efficiency.
[0083] Example 1
[0084] S1: Prepare the perovskite light absorbing layer precursor solution: PbI2, CsI, FAI and DMSO are dissolved in DMF solvent at a molar ratio of 1:0.05:0.95:1, and stirred continuously for 2 hours under heating at 60°C until completely dissolved to obtain FA with a concentration of 1.2 mol / L. 0.95 Cs 0.05 PbI3 perovskite light absorbing layer precursor solution.
[0085] S2: The substrate composed of the conductive glass / SnO2 layer is annealed in an air atmosphere at 150°C for 30 minutes, and the substrate is transferred to a glove box after the temperature drops to room temperature.
[0086] S3: FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was spin-coated on a conductive glass substrate at a speed of 4000 rpm for 30 seconds, and then heated at 150°C to contain FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was added to a conductive glass substrate for 20 minutes to obtain a perovskite light absorbing layer.
[0087] S4: Preparation of N, N-dimethylbenzimidazole iodide: First, 20.0 mmol of benzimidazole, 22.0 mmol of K2CO3 and 50 mL of CH3CN were mixed, and after uniform stirring for 2 hours, 45.0 mmol of methyl iodide was added dropwise to obtain a mixed solution. The mixed solution was stirred at 85°C for 72 hours, and then the stirred product was extracted with 100 mL of CH2Cl2, and the organic phase obtained by extraction was dried overnight with MgSO4 to obtain N, N-dimethylbenzimidazole iodide.
[0088] S5: Dissolve N,N-dimethylbenzimidazole iodide in isopropanol to obtain a 3 mg / mL N,N-dimethylbenzimidazole iodide solution, and spin-coat it on the perovskite light-absorbing layer at a speed of 5000 rpm for 30 seconds. After the spin-coating, heat at 100°C for 5 minutes, and then anneal to obtain a one-dimensional structured modified layer.
[0089] S6: Add tetra-tert-butylpyridine (TBP) and lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) to a chlorobenzene solution of spiro-OMeTAD with a hole transport layer material concentration of 40 mg / mL, mix thoroughly, and then spin-coat on the perovskite light absorbing layer to form a hole transport layer.
[0090] S7: Using a thermal evaporation method, a gold back electrode layer is evaporated on the perovskite light absorbing layer coated with spiro-OMeTAD.
[0091] In this embodiment, the thickness of the perovskite light absorption layer is 400 nm, the thickness of the hole transport layer is 100 nm, and the thickness of the gold back electrode layer is 80 nm.
[0092] Photoelectric conversion performance test:
[0093] The perovskite solar cell prepared in this embodiment was subjected to a performance test, and its photoelectric conversion efficiency reached 20.01%.
[0094] Example 2
[0095] S1: Prepare the perovskite light absorbing layer precursor solution: PbI2, CsI, FAI and DMSO are dissolved in DMF solvent at a molar ratio of 1:0.05:0.95:1, and stirred continuously for 2 hours under heating at 60°C until completely dissolved to obtain FA with a concentration of 1.2 mol / L. 0.95 Cs 0.05 PbI3 perovskite light absorbing layer precursor solution.
[0096] S2: The substrate composed of the conductive glass / SnO2 layer is annealed in an air atmosphere at 150°C for 30 minutes, and the substrate is transferred to a glove box after the temperature drops to room temperature.
[0097] S3: FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was spin-coated on a conductive glass substrate at a speed of 4000 rpm for 30 seconds, and then heated at 150°C to contain FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was added to a conductive glass substrate for 20 minutes to obtain a perovskite light absorbing layer.
[0098] S4: Preparation of N, N-diethylbenzimidazole iodide: First, 20.0 mmol of benzimidazole, 22.0 mmol of K2CO3 and 50 mL of CH3CN were mixed, and after uniform stirring for 2 hours, 45.0 mmol of ethyl iodide was added dropwise to obtain a mixed solution. The mixed solution was stirred at 85°C for 72 hours, and then the stirred product was extracted with 100 mL of CH2Cl2, and the organic phase obtained by extraction was dried overnight with MgSO4 to obtain N, N-diethylbenzimidazole iodide.
[0099] S5: Dissolve N,N-diethylbenzimidazole iodide in isopropanol to obtain a 3 mg / mL N,N-diethylbenzimidazole iodide solution, and spin-coat it on the perovskite light-absorbing layer at a speed of 5000 rpm for 30 seconds. After the spin-coating, heat at 100°C for 5 minutes, and then anneal to obtain a one-dimensional structured modified layer.
[0100] S6: Add tetra-tert-butylpyridine (TBP) and lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) to a chlorobenzene solution of spiro-OMeTAD with a hole transport layer material concentration of 40 mg / mL, mix thoroughly, and then spin-coat on the perovskite light absorbing layer to form a hole transport layer.
[0101] S7: Using a thermal evaporation method, a gold back electrode layer is evaporated on the perovskite light absorbing layer coated with spiro-OMeTAD.
[0102] In this embodiment, the thickness of the perovskite light absorption layer is 400 nm, the thickness of the hole transport layer is 100 nm, and the thickness of the gold back electrode layer is 80 nm.
[0103] Photoelectric conversion performance test:
[0104] The perovskite solar cell prepared in this embodiment was subjected to a performance test, and its photoelectric conversion efficiency reached 20.07%.
[0105] Example 3
[0106] S1: Prepare the perovskite light absorbing layer precursor solution: PbI2, CsI, FAI and DMSO are dissolved in DMF solvent at a molar ratio of 1:0.05:0.95:1, and stirred continuously for 2 hours under heating at 60°C until completely dissolved to obtain FA with a concentration of 1.2 mol / L. 0.95 Cs 0.05 PbI3 perovskite light absorbing layer precursor solution.
[0107] S2: The substrate composed of the conductive glass / SnO2 layer is annealed in an air atmosphere at 150°C for 30 minutes, and the substrate is transferred to a glove box after the temperature drops to room temperature.
[0108] S3: FA0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was spin-coated on a conductive glass substrate at a speed of 4000 rpm for 30 seconds, and then heated at 150°C to contain FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was added to a conductive glass substrate for 20 minutes to obtain a perovskite light absorbing layer.
[0109] S4: Prepare N, N-diisopropylbenzimidazole iodide, first mix 20.0mmol benzimidazole, 22.0mmol K2CO3 and 50mL CH3CN, stir evenly for 2 hours, then add 45.0mmol isopropyl iodide dropwise to obtain a mixed solution. Stir the mixed solution at 85°C for 3 days, then extract the stirred product with 100mL CH2Cl2, and dry the organic phase obtained by extraction with MgSO4 overnight to obtain N, N-diisopropylbenzimidazole iodide.
[0110] S5: Dissolve N,N-diisopropylbenzimidazole iodide in isopropanol to obtain a 3 mg / mL N,N-diisopropylbenzimidazole iodide solution, and spin-coat it on the perovskite light-absorbing layer at a speed of 5000 rpm for 30 seconds. After the spin-coating, heat at 100°C for 5 minutes, and then anneal to obtain a one-dimensional structured modified layer. Figure 3 is the N, N-diisopropylbenzimidazole iodide in Example 3 of the present invention. 1 H NMR characterization diagram, NMR data proves that the preparation method of the present invention forms an iodinated N, N-diisopropylbenzimidazole structure.
[0111] S6: Add tetra-tert-butylpyridine (TBP) and lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) to a chlorobenzene solution of spiro-OMeTAD with a hole transport layer material concentration of 40 mg / mL, mix thoroughly, and then spin-coat on the perovskite light absorbing layer to form a hole transport layer.
[0112] S7: Using a thermal evaporation method, a gold back electrode layer is evaporated on the perovskite light absorbing layer coated with spiro-OMeTAD.
[0113] In this embodiment, the thickness of the perovskite light absorption layer is 400 nm, the thickness of the hole transport layer is 100 nm, and the thickness of the gold back electrode layer is 80 nm.
[0114] Photoelectric conversion performance test:
[0115] The perovskite solar cell prepared in this embodiment was subjected to a performance test, and its photoelectric conversion efficiency reached 20.92%.
[0116] Example 4
[0117] S1: Prepare the perovskite light absorbing layer precursor solution: PbI2, CsI, FAI and DMSO are dissolved in DMF solvent at a molar ratio of 1:0.05:0.95:1, and stirred continuously for 2 hours under heating at 60°C until completely dissolved to obtain FA with a concentration of 1.2 mol / L. 0.95 Cs 0.05 PbI3 perovskite light absorbing layer precursor solution.
[0118] S2: The substrate composed of the conductive glass / SnO2 layer is annealed in an air atmosphere at 150°C for 30 minutes, and the substrate is transferred to a glove box after the temperature drops to room temperature.
[0119] S3: FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was spin-coated on a conductive glass substrate at a speed of 4000 rpm for 30 seconds, and then heated at 150°C to contain FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was added to a conductive glass substrate for 20 minutes to obtain a perovskite light absorbing layer.
[0120] S4: Preparation of N, N-dihexylbenzimidazole iodide: First, 20.0mmol benzimidazole, 22.0mmol K2CO3 and 50mL CH3CN were mixed, and after uniform stirring for 2 hours, 45.0mmol hexyl iodide was added dropwise to obtain a mixed solution. The mixed solution was stirred at 85°C for 72h, and then the stirred product was extracted with 100mL CH2Cl2, and the organic phase obtained by extraction was dried overnight with MgSO4 to obtain N, N-dihexylbenzimidazole iodide.
[0121] S5: Dissolve N,N-dihexylbenzimidazole iodide in isopropanol to obtain a 3 mg / mL N,N-dihexylbenzimidazole iodide solution, and spin-coat it on the perovskite light-absorbing layer at a speed of 5000 rpm for 30 seconds. After the spin-coating, heat at 100°C for 5 minutes, and then anneal to obtain a one-dimensional structured modified layer.
[0122] S6: Add tetra-tert-butylpyridine (TBP) and lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) to a chlorobenzene solution of spiro-OMeTAD with a hole transport layer material concentration of 40 mg / mL, mix thoroughly, and then spin-coat on the perovskite light absorbing layer to form a hole transport layer.
[0123] S7: Using a thermal evaporation method, a gold back electrode layer is evaporated on the perovskite light absorbing layer coated with spiro-OMeTAD.
[0124] In this embodiment, the thickness of the perovskite light absorption layer is 400 nm, the thickness of the hole transport layer is 100 nm, and the thickness of the gold back electrode layer is 80 nm.
[0125] Photoelectric conversion performance test:
[0126] The perovskite solar cell prepared in this embodiment was subjected to a performance test, and its photoelectric conversion efficiency reached 20.03%.
[0127] Example 5
[0128] S1: Prepare the perovskite light absorbing layer precursor solution: PbI2, CsI, FAI and DMSO are dissolved in DMF solvent at a molar ratio of 1:0.05:0.95:1, and stirred continuously for 2 hours under heating at 60°C until completely dissolved to obtain FA with a concentration of 1.2 mol / L. 0.95 Cs 0.05 PbI3 perovskite light absorbing layer precursor solution.
[0129] S2: The substrate composed of the conductive glass / SnO2 layer is annealed in an air atmosphere at 150°C for 30 minutes, and the substrate is transferred to a glove box after the temperature drops to room temperature.
[0130] S3: FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was spin-coated on a conductive glass substrate at a speed of 4000 rpm for 30 seconds, and then heated at 150°C to contain FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was added to a conductive glass substrate for 20 minutes to obtain a perovskite light absorbing layer.
[0131] S4: Preparation of N, N-diisopropylbenzimidazole bromide: First, 20.0 mmol of benzimidazole, 22.0 mmol of K2CO3 and 50 mL of CH3CN were mixed, and after uniform stirring for 2 hours, 45.0 mmol of isopropyl bromide was added dropwise to obtain a mixed solution. The mixed solution was stirred at 85°C for 72 hours, and then the stirred product was extracted with 100 mL of CH2Cl2, and the organic phase obtained by extraction was dried overnight with MgSO4 to obtain N, N-diisopropylbenzimidazole bromide.
[0132] S5: Dissolve N,N-diisopropylbenzimidazole bromide in isopropanol to obtain a 3 mg / mL N,N-diisopropylbenzimidazole bromide solution, and spin-coat it on the perovskite light-absorbing layer at a speed of 5000 rpm for 30 seconds. After the spin-coating, heat at 100°C for 5 minutes, and then anneal to obtain a one-dimensional structured modified layer.
[0133] S6: Add tetra-tert-butylpyridine (TBP) and lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) to a chlorobenzene solution of spiro-OMeTAD with a hole transport layer material concentration of 40 mg / mL, mix thoroughly, and then spin-coat on the perovskite light absorbing layer to form a hole transport layer.
[0134] S7: Using a thermal evaporation method, a gold back electrode layer is evaporated on the perovskite light absorbing layer coated with spiro-OMeTAD.
[0135] In this embodiment, the thickness of the passivated perovskite light absorption layer is 400 nm, the thickness of the hole transport layer is 100 nm, and the thickness of the gold back electrode layer is 80 nm.
[0136] Photoelectric conversion performance test:
[0137] The perovskite solar cell prepared in this embodiment was subjected to a performance test, and its photoelectric conversion efficiency reached 20.15%.
[0138] Example 6
[0139] S1: Prepare the perovskite light absorbing layer precursor solution: PbI2, CsI, FAI and DMSO are dissolved in DMF solvent at a molar ratio of 1:0.05:0.95:1, and stirred continuously for 2 hours under heating at 60°C until completely dissolved to obtain FA with a concentration of 1.2 mol / L. 0.95 Cs 0.05 PbI3 perovskite light absorbing layer precursor solution.
[0140] S2: The substrate composed of the conductive glass / SnO2 layer is annealed in an air atmosphere at 150°C for 30 minutes, and the substrate is transferred to a glove box after the temperature drops to room temperature.
[0141] S3: FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was spin-coated on a conductive glass substrate at a speed of 4000 rpm for 30 seconds, and then heated at 150°C to contain FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was added to a conductive glass substrate for 20 minutes to obtain a perovskite light absorbing layer.
[0142] S4: Preparation of N, N-diisopropylbenzimidazole chloride: First, 20.0mmol benzimidazole, 22.0mmol K2CO3 and 50mL CH3CN were mixed, and after uniform stirring for 2 hours, 45.0mmol isopropyl chloride was added dropwise to obtain a mixed solution. The mixed solution was stirred at 85°C for 72h, and the stirred product was extracted with 100mL CH2C12, and the organic phase obtained by extraction was dried overnight with MgSO4 to obtain N, N-diisopropylbenzimidazole chloride.
[0143] S5: Dissolve N,N-diisopropylbenzimidazole chloride in isopropanol to obtain a 3 mg / mL N,N-diisopropylbenzimidazole chloride solution, and spin-coat it on the perovskite light-absorbing layer at a speed of 5000 rpm for 30 seconds. After the spin-coating, heat at 100°C for 5 minutes, and then anneal to obtain a one-dimensional structured modified layer.
[0144] S6: Add tetra-tert-butylpyridine (TBP) and lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) to a chlorobenzene solution of spiro-OMeTAD with a hole transport layer material concentration of 40 mg / mL, mix thoroughly, and then spin-coat on the perovskite light absorbing layer to form a hole transport layer.
[0145] S7: Using a thermal evaporation method, a gold back electrode layer is evaporated on the perovskite light absorbing layer coated with spiro-OMeTAD.
[0146] In this embodiment, the thickness of the passivated perovskite light absorption layer is 400 nm, the thickness of the hole transport layer is 100 nm, and the thickness of the gold back electrode layer is 80 nm.
[0147] Photoelectric conversion performance test:
[0148] The perovskite solar cell prepared in this embodiment was subjected to a performance test, and its photoelectric conversion efficiency reached 20.25%.
[0149] Example 7
[0150] S1: Prepare the perovskite light absorbing layer precursor solution: PbI2, CsI, FAI and DMSO are dissolved in DMF solvent at a molar ratio of 1:0.05:0.95:1, and stirred continuously for 2 hours under heating at 60°C until completely dissolved to obtain FA with a concentration of 1.2 mol / L. 0.95 Cs 0.05 PbI3 perovskite light absorbing layer precursor solution.
[0151] S2: On a 6cm x 6cm FTO conductive glass substrate, a P1 scribe line is etched by laser to separate the sub-cells. The laser power is 18W and the width range is 200um.
[0152] S3: The perovskite light absorbing layer precursor solution is scraped onto the divided conductive glass substrate, and then heated at 150°C to form a FA 0.95 Cs 0.05 The substrate is treated with a PbI3 perovskite light-absorbing layer precursor solution for 20 minutes to form a perovskite light-absorbing layer; subsequently, a P2 scribe line is etched by laser with a laser power of 10W and a width range of 500um.
[0153] S4: Prepare N, N-diisopropylbenzimidazole iodide, first mix 20.0mmol benzimidazole, 22.0mmol K2CO3 and 50mL CH3CN, stir evenly for 2 hours, then add 45.0mmol isopropyl iodide dropwise to obtain a mixed solution. Stir the mixed solution at 85°C for 72h, then extract the stirred product with 100mL CH2Cl2, and dry the organic phase obtained by extraction with MgSO4 overnight to obtain N, N-diisopropylbenzimidazole iodide.
[0154] S5: Dissolve N,N-diisopropylbenzimidazole iodide in isopropanol to obtain a 3 mg / mL N,N-diisopropylbenzimidazole iodide solution, and spin-coat it on the perovskite light-absorbing layer at a speed of 5000 rpm for 30 seconds. After the spin-coating, heat at 100°C for 5 minutes, and then anneal to obtain a one-dimensional structured modified layer.
[0155] S6: Add tetra-tert-butylpyridine (TBP) and lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) to a chlorobenzene solution of spiro-OMeTAD with a hole transport layer material concentration of 40 mg / mL, mix thoroughly, and then coat the solution on the perovskite light absorbing layer to form a hole transport layer. Then, laser etching is used to form a P3 scribe track with a laser power of 10 W and a width range of 200 um.
[0156] S7: evaporate the gold back electrode layer and use laser to etch the P4 scribe line with a laser power of 7W and a width range of 200um.
[0157] In this embodiment, the thickness of the perovskite light absorption layer is 400 nm, the thickness of the hole transport layer is 100 nm, and the thickness of the gold back electrode layer is 80 nm.
[0158] Photoelectric conversion performance test:
[0159] The performance of the perovskite solar cell prepared in this embodiment was tested, and its photoelectric conversion efficiency reached 15.11% with a total area of 36 cm 2 , active area 18cm 2 .
[0160] Example 8
[0161] S1: Prepare the perovskite light absorbing layer precursor solution: PbI2, CsI, FAI and DMSO are dissolved in DMF solvent at a molar ratio of 1:0.05:0.95:1, and stirred continuously for 2 hours under heating at 60°C until completely dissolved to obtain FA with a concentration of 1.2 mol / L. 0.95 Cs 0.05 PbI3 perovskite light absorbing layer precursor solution.
[0162] S2: The substrate composed of the conductive glass / SnO2 layer is annealed in an air atmosphere at 150°C for 30 minutes, and the substrate is transferred to a glove box after the temperature drops to room temperature.
[0163] S3: FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was spin-coated on a conductive glass substrate at a speed of 4000 rpm for 30 seconds, and then heated at 150°C to contain FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was added to a conductive glass substrate for 20 minutes to obtain a perovskite light absorbing layer.
[0164] S4: Preparation of a mixture of N, N-dihexylbenzimidazole iodide and N, N-diisopropylbenzimidazole iodide: First, 20.0 mmol of benzimidazole, 22.0 mmol of K2CO3 and 50 mL of CH3CN were mixed, and after uniform stirring for 2 hours, 20.0 mmol of hexyl iodide and 25.0 mmol of isopropyl iodide were added dropwise to obtain a mixed solution. The mixed solution was stirred at 85°C for 72 hours, and the stirred product was extracted with 100 mL of CH2Cl2, and the organic phase obtained by the extraction was dried overnight with MgSO4 to obtain a mixture of N, N-dihexylbenzimidazole iodide and N, N-diisopropylbenzimidazole iodide.
[0165] S5: Dissolve the mixture of N, N-dihexylbenzimidazole iodide and N, N-diisopropylbenzimidazole iodide in isopropanol to obtain a 1-2 mg / mL N, N-dihexylbenzimidazole iodide solution and a 1-2 mg / mL N, N-diisopropylbenzimidazole iodide solution, and spin-coat them on the perovskite light-absorbing layer at a speed of 5000 rpm for 30 seconds, then heat at 100°C for 5 minutes, and then anneal to obtain a one-dimensional structured modification layer.
[0166] S6: Add tetra-tert-butylpyridine (TBP) and lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) to a chlorobenzene solution of spiro-OMeTAD with a hole transport layer material concentration of 40 mg / mL, mix thoroughly, and then spin-coat on the perovskite light absorbing layer to form a hole transport layer.
[0167] S7: Using a thermal evaporation method, a gold back electrode layer is evaporated on the perovskite light absorbing layer coated with spiro-OMeTAD.
[0168] In this embodiment, the thickness of the perovskite light absorption layer is 400 nm, the thickness of the hole transport layer is 100 nm, and the thickness of the gold back electrode layer is 80 nm.
[0169] In an embodiment of the present invention, the halogenated N,N-dialkylbenzimidazole salt prepared in step S4 can also be selected from one or more of N,N-dimethylbenzimidazole iodide, N,N-diethylbenzimidazole iodide, N,N-diisopropylbenzimidazole iodide, and N,N-dihexylbenzimidazole iodide; for example, a combination of N,N-dimethylbenzimidazole iodide and N,N-diisopropylbenzimidazole iodide, or a combination of three halogenated N,N-dialkylbenzimidazole salts of N,N-dimethylbenzimidazole iodide, N,N-diethylbenzimidazole iodide and N,N-dihexylbenzimidazole iodide, and other combinations.
[0170] Comparative Example 1
[0171] S1: Prepare the perovskite light absorbing layer precursor solution: PbI2, CsI, FAI and DMSO are dissolved in DMF solvent at a molar ratio of 1:0.05:0.95:1, and stirred continuously for 2 hours under heating at 60°C until completely dissolved to obtain FA with a concentration of 1.2 mol / L. 0.95 Cs 0.05 PbI3 perovskite light absorbing layer precursor solution.
[0172] S2: The substrate composed of the conductive glass / SnO2 layer is annealed in an air atmosphere at 150°C for 30 minutes, and the substrate is transferred to a glove box after the temperature drops to room temperature.
[0173] S3: FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was spin-coated on a conductive glass substrate at a speed of 4000 rpm for 30 seconds, and then heated at 150°C to contain FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was added to a conductive glass substrate for 20 minutes to obtain a perovskite light absorbing layer.
[0174] S5: Add tetra-tert-butylpyridine (TBP) and lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) to a chlorobenzene solution of spiro-OMeTAD with a hole transport layer material concentration of 40 mg / mL, mix well, and then spin-coat on the perovskite light absorbing layer to form a hole transport layer.
[0175] S7: Using a thermal evaporation method, a gold back electrode layer is evaporated on the perovskite light absorbing layer coated with spiro-OMeTAD.
[0176] In this comparative example, the thickness of the perovskite light absorption layer is 400 nm, the thickness of the hole transport layer is 100 nm, and the thickness of the gold back electrode layer is 80 nm.
[0177] Photoelectric conversion performance test:
[0178] The perovskite solar cell prepared in this comparative example was subjected to a performance test, and its photoelectric conversion efficiency reached 19.35%.
[0179] Table 1
[0180]
[0181] As can be seen from Table 1, the perovskite solar cells obtained by spin-coating the perovskite light-absorbing layer with the halogenated N, N-dialkylbenzimidazole salt proposed in the present invention to prepare the modified layer in Examples 1-6 have a significantly improved photoelectric conversion efficiency of more than 20% compared to the unmodified perovskite solar cell in Comparative Example 1.
[0182] Figure 4 From the XRD patterns of the one-dimensional structure modification layers prepared based on different halogenated N,N-dialkylbenzimidazole salts in Examples 1-4 of the present invention and Comparative Example 1, it can be seen that as the alkyl chain becomes longer, the characteristic peak of the one-dimensional perovskite decreases from 8.86° of the one-dimensional perovskite based on N,N-dimethylbenzimidazole to 7.88° of the one-dimensional perovskite based on N,N-dihexylbenzimidazole, indicating that the gap in the one-dimensional structure increases with the increase of the carbon chain.
[0183] Figure 5 The efficiency curve comparison of the perovskite solar cell based on the one-dimensional structure modification layer prepared by different halogenated N, N-dialkylbenzimidazole salts in Examples 1-4 of the present invention and Comparative Example 1 is shown in Figure 1. The corresponding perovskite prepared is used to assemble the battery. The JV characteristic curve is as follows: Figure 5 As shown, the study found that different one-dimensional structures obtained by the preparation method of the present invention can improve the efficiency of the battery, among which N, N-diisopropylbenzimidazole has the best effect and the efficiency can reach 20.92%.
[0184] Comparative Example 2
[0185] S1: Prepare the perovskite light absorbing layer precursor solution: PbI2, CsI, FAI and DMSO are dissolved in DMF solvent at a molar ratio of 1:0.05:0.95:1, and stirred continuously for 2 hours under heating at 60°C until completely dissolved to obtain FA with a concentration of 1.2 mol / L. 0.95 Cs0.05 PbI3 perovskite light absorbing layer precursor solution.
[0186] S2: The substrate composed of the conductive glass / SnO2 layer is annealed in an air atmosphere at 150°C for 30 minutes, and the substrate is transferred to a glove box after the temperature drops to room temperature.
[0187] S3: FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was spin-coated on a conductive glass substrate at a speed of 4000 rpm for 30 seconds, and then heated at 150°C to contain FA 0.95 Cs 0.05 The PbI3 perovskite light absorbing layer precursor solution was added to a conductive glass substrate for 20 minutes to obtain a perovskite light absorbing layer.
[0188] S4: Preparation of imidazole iodide: First, 20.0mmol imidazole, 22.0mmol K2CO3 and 50mL CH3CN were mixed, and after uniform stirring for 2 hours, 45.0mmol hydroiodic acid (47% by mass in aqueous solution) was added dropwise to obtain a mixed solution. The mixed solution was stirred at 85°C for 72h, and then the stirred product was extracted with 100mL CH2Cl2, and the organic phase obtained by extraction was dried overnight with MgSO4 to obtain imidazole iodide.
[0189] S5: Dissolve imidazole iodide in isopropanol to obtain an imidazole iodide solution with a concentration of 3 mg / mL, and spin-coat it on the perovskite light-absorbing layer at a speed of 5000 rpm for 30 seconds. After the spin-coating, heat it at 100°C for 5 minutes, and then anneal it to obtain the modified layer.
[0190] S6: Add tetra-tert-butylpyridine (TBP) and lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) to a chlorobenzene solution of spiro-OMeTAD with a hole transport layer material concentration of 40 mg / mL, mix thoroughly, and then spin-coat on the perovskite light absorbing layer to form a hole transport layer.
[0191] S7: Using a thermal evaporation method, a gold back electrode layer is evaporated on the perovskite light absorbing layer coated with spiro-OMeTAD.
[0192] In this comparative example, the thickness of the perovskite light absorption layer is 400 nm, the thickness of the hole transport layer is 100 nm, and the thickness of the gold back electrode layer is 80 nm.
[0193] Photoelectric conversion performance test:
[0194] The perovskite solar cell prepared in this comparative example was subjected to a performance test, and its photoelectric conversion efficiency reached 19.42%.
[0195] Table 2
[0196]
[0197] Comparative Example 2: Imidazole iodide is used to prepare the modified layer on the surface of the perovskite light absorbing layer. From the data in Table 2 and Figure 6 It can be seen that compared with the perovskite solar cell without a modified layer, the perovskite solar cell prepared by using imidazole cation modification has a slight improvement in photoelectric conversion efficiency. However, compared with the treatment effect of imidazole cation, it can be seen that the effect of benzimidazole treatment is particularly obvious. The experimentally obtained photoelectric conversion efficiency of 20.92% is much higher than the efficiency of 19.42% of the device after only imidazole treatment. Figure 6 It can be seen that the humidity stability of the device treated with benzimidazole is also better than that of the device treated with imidazole. Figure 7 The cell efficiency curve comparison diagram of the perovskite solar cell based on the one-dimensional structure modification layer prepared by different halogen anions in the present invention is shown in FIG. Figure 7 Further research on the effect of different halogen anions found that the efficiency of the device after treatment with different halogens did not change much, which shows that the effect of the benzene ring and the substituents is more obvious. Different halogens have little effect on the efficiency of the device, highlighting the importance of the van der Waals force between different benzimidazole cations.
[0198] Comparative Example 3
[0199] S1: Prepare the perovskite light absorbing layer precursor solution: PbI2, CsI, FAI and DMSO are dissolved in DMF solvent at a molar ratio of 1:0.05:0.95:1, and stirred continuously for 2 hours under heating at 60°C until completely dissolved to obtain FA with a concentration of 1.2 mol / L. 0.95 Cs 0.05 PbI3 perovskite light absorbing layer precursor solution.
[0200] S2: On a 6cm x 6cm FTO conductive glass substrate, a P1 scribe line is etched by laser to separate the sub-cells. The laser power is 18W and the width range is 200um.
[0201] S3: The perovskite light absorbing layer precursor solution is scraped onto the divided conductive glass substrate, and then heated at 150°C to form a FA 0.95 Cs 0.05 The substrate is treated with a PbI3 perovskite light-absorbing layer precursor solution for 20 minutes to form a perovskite light-absorbing layer; subsequently, a P2 scribe line is etched by laser with a laser power of 10W and a width range of 500um.
[0202] S4: Add tetra-tert-butylpyridine (TBP) and lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) to a chlorobenzene solution of spiro-OMeTAD with a hole transport layer material concentration of 40 mg / mL, mix thoroughly, and then coat it on the perovskite light absorption layer to form a hole transport layer. Then, laser etching is used to form a P3 scribe track with a laser power of 10 W and a width range of 200 um.
[0203] S5: evaporate the gold back electrode layer and use laser to etch the P4 scribe line with a laser power of 7W and a width range of 200um.
[0204] In this comparative example, the thickness of the perovskite light absorption layer is 400 nm, the thickness of the hole transport layer is 100 nm, and the thickness of the gold back electrode layer is 80 nm.
[0205] Photoelectric conversion performance test:
[0206] The performance of the perovskite solar cell prepared in this comparative example was tested, and its photoelectric conversion efficiency reached 12.70% with a total area of 36 cm 2 , active area 18cm 2 .
[0207] Table 3
[0208]
[0209] Figure 8 The module efficiency curve comparison diagram (a) and stability curve comparison diagram (b) before and after the one-dimensional structure modification layer is passivated in Example 7 of the present invention and Comparative Example 3. It can be seen from the data in Table 3 that by using the preparation method of the present invention, N, N-diisopropylbenzimidazole iodide is used for large-area module preparation, and the photoelectric conversion efficiency of the obtained perovskite solar cell is greatly improved. The module efficiency obtained in Comparative Example 3 is only 12.70%, while the perovskite solar cell module efficiency protected by the one-dimensional structure modification layer can reach 15.11%, which is significantly improved. It is precisely because the one-dimensional passivation structure modification layer inhibits the vertical and lateral migration and diffusion of ions that the module stability based on the one-dimensional passivation layer structure is excellent.
[0210] The above embodiments are only used to illustrate the principles and effects of the present invention, and are not used to limit the present invention. Anyone skilled in the art may modify the above embodiments without violating the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be as listed in the claims.
Claims
1. A perovskite solar cell, comprising a conductive substrate, an electron transport layer, a perovskite light absorbing layer, a modification layer, a hole transport layer and a back electrode layer stacked in sequence, characterized in that: The modified layer is a one-dimensional passivation layer; the general formula of the perovskite light absorption layer material is ABX n The general formula of the modified layer material is MBX n , wherein M is N,N-dialkylbenzimidazolyl, and the N,N-dialkylbenzimidazolyl is selected from at least one of N,N-dimethylbenzimidazolyl, N,N-diethylbenzimidazolyl, N,N-diisopropylbenzimidazolyl and N,N-dihexylbenzimidazolyl; A is selected from C6H5C2H4NH3 + 、CH3C3H6NH3 + 、COOH(CH2)4NH3 + 、CH3NH3 + 、HC(NH2)2 + , Cs + and Rb + At least one of; The B is Pb 2+ Sn 2+ and Ge 2+ At least one of; The X is a halogen ion; n is 3.
2. The perovskite solar cell according to claim 1, characterized in that The thickness of the modified layer is 5-40 nm.
3. A method for preparing a perovskite solar cell according to claim 1, characterized in that: The following steps are involved: S1: Configuration perovskite (ABX n ) a light absorbing layer precursor solution, wherein X is a halogen ion; S2: pre-treated conductive glass / electron transport layer substrate; S3: coating the precursor solution prepared in S1 on the substrate, and then annealing the substrate to obtain perovskite (ABX n ) light absorbing layer; S4: Preparation of halogenated N, N-dialkylbenzimidazole salt: firstly, benzimidazole, K2CO3 and CH3CN are mixed, stirred, and then alkyl halide is added dropwise to obtain a mixed solution, stirred, extracted and dried to obtain halogenated N, N-dialkylbenzimidazole salt; the halogen element in the alkyl halide and the perovskite (ABX n )The X elements in the light-absorbing layer are consistent; S5: Dissolve the prepared N,N-dialkylbenzimidazole halogenide in an organic solvent and apply it by scraping or spin coating on the perovskite (ABX n ) on the light absorbing layer, annealing to obtain a modified layer, wherein the modified layer is a one-dimensional passivation layer; S6: forming a hole transport layer on the surface of the modified layer; S7: forming a back electrode layer on the surface of the hole transport layer.
4. The preparation method according to claim 3, characterized in that: In step S4, the alkyl halide is selected from at least one of methyl iodide, ethyl iodide, hexyl iodide, isopropyl iodide, methyl bromide, ethyl bromide, hexyl bromide, isopropyl bromide, methyl chloride, ethyl chloride, hexyl chloride, and isopropyl chloride.
5. The preparation method according to claim 3, characterized in that: In the step S4, the stirring temperature of the mixed solution is 80 to 120° C., and the stirring time is 48 to 120 hours.
6. The preparation method according to claim 3, characterized in that: In the step S5, the concentration of the halogenated N,N-dialkylbenzimidazole salt in the organic solvent is 0.5-10 mg / mL.
7. The preparation method according to claim 3, characterized in that: In step S5, the spin coating speed is 4000-6000 rpm / mim, and the spin coating time is 20-50s; the scraping speed is 50-500mms -1 .
8. The preparation method according to claim 3, characterized in that: In the step S5, the heating temperature of the annealing treatment is 50-200° C., and the heating time is 5-30 min.
9. The preparation method according to claim 3, characterized in that: In the step S5, the thickness of the modified layer is 5-40 nm.
10. The preparation method according to claim 3, characterized in that: In step S5, the organic solvent is selected from at least one of isopropanol, methanol, dichloroethane, chloroform, and chlorobenzene.